Debittering of bitter gourd juice using β-cyclodextrin: Mechanism and effect on antidiabetic potential. (1st October 2018) - Deshaware, Shweta; Gupta, Sumit; Singhal, Rekha S.; Joshi, Mamata; Variyar, Prasad S.
Highlights: Completely debitter bitter gourd juice prepared by adding β- cyclodextrin. Addition of β- cyclodextrin led to slight (10%) reduction in antidiabetic activity. Total phenolic and antioxidant activity increased due to β- cyclodextrin. β- Cyclodextrin - momordicosides (bitter components) complexes studied by NMR and FTIR. Abstract: Triterpene glycosides namely momordicoside K and momordicoside L causes bitterness in bitter-gourd thereby reducing its consumer acceptance. Reducing bitterness of the juice by addition of β -cyclodextrin (0.25–2%) was attempted and its effect on sensory quality, total phenolic content, antioxidant activity and antidiabetic potential was evaluated. Juice with 1.5% β -cyclodextrin demonstrated highest score (7.7 ± 0.3) for sensory acceptability compared to the control (3.8 ± 0.7). A significantly (p < 0.05) higher total phenolic content and antioxidant activity was observed. A marginal (10%) but significant (p < 0.05) reduction in α-glucosidase inhibition activity without affecting α-amylase activity was noted. Results from NMR, ROESY and FTIR studies indicated formation of an inclusion complex by interaction of hydrophobic triterpenoidal region of momordicosides with β -cyclodextrin.